2002
DOI: 10.1074/jbc.m206402200
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling Protects 3T3-L1 Preadipocytes from Apoptosis through Induction of Insulin-like Growth Factors

Abstract: Ectopic expression of Wnt-1 in 3T3-L1 preadipocytes stabilizes ␤-catenin, activates TCF-dependent gene transcription, and blocks adipogenesis. Here we report that upon serum withdrawal, Wnt-1 causes 3T3-L1 cells to resist apoptosis through a mechanism that is partially dependent on phosphatidylinositol 3-kinase. Although activation of Wnt signaling by inhibition of GSK-3 activity or ectopic expression of dominant stable ␤-catenin blocks apoptosis, inhibition of Wnt signaling through expression of dominant nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(138 citation statements)
references
References 52 publications
9
127
2
Order By: Relevance
“…Evidence for the dependence of Wnt1 on the Akt pathway can be drawn from a variety of cell populations. For example, PC12 cell differentiation that is dependent upon Wnt1 signaling and trophic factor induction is blocked during the repression of Akt activity [38], Wnt1 has been shown in preadipocytes to increase Akt phosphorylation [39], and the Wnt1-induced secreted protein in a fibroblast cell line uses Akt to block apoptotic death [40]. We show that Wnt1 overexpression independently increases the phosphorylation and the activation of Akt1 to a significantly greater degree than Aβ 1-42 alone, suggesting that Wnt1 uses Akt1 activation to promote neuronal protection.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the dependence of Wnt1 on the Akt pathway can be drawn from a variety of cell populations. For example, PC12 cell differentiation that is dependent upon Wnt1 signaling and trophic factor induction is blocked during the repression of Akt activity [38], Wnt1 has been shown in preadipocytes to increase Akt phosphorylation [39], and the Wnt1-induced secreted protein in a fibroblast cell line uses Akt to block apoptotic death [40]. We show that Wnt1 overexpression independently increases the phosphorylation and the activation of Akt1 to a significantly greater degree than Aβ 1-42 alone, suggesting that Wnt1 uses Akt1 activation to promote neuronal protection.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of selected target genes, such as Cyclin-D1 (Shtutman et al, 1999;Tetsu and McCormick, 1999), IGF2 (Longo et al, 2002) and TCF4 (Kolligs et al, 2002) was measured by real-time semi quantitative PCR ( Figure 2c). Significant increases of Cyclin-D1 (2.45 ± 0.32-and 1.86 ± 0.25-fold increase) and IGF2 expression (2.9 ± 0.07-and 1.38 ± 0.09-fold increase) were detected in LAN-1-R and IGRN-91-R, respectively.…”
Section: Identification Of Differentially Expressed Genes In Chemoresmentioning
confidence: 99%
“…Adipocytes are hormonally active and adipocytokines are able to elicit a response from beta cells [5]. Studies have shown that adipocytes secrete Wnt signalling molecules to regulate adipocyte differentiation [9][10][11]. In a previous study we demonstrated that Wnt3a and Wnt10b are secreted by mature human adipocytes and regulate hormone secretion from adrenocortical cells in vitro [12].…”
mentioning
confidence: 99%